Virtual Internationalization in Higher Education: Design Reflections and Lessons Learned - Kateryna Holubinka; Christian M. Stracke; Panu Forsman; Sanna Juutinen (Forum Neue Medien in der Lehre Austria, 2021)
In response to ever-increasing demands for internationally and interculturally competent educational experts, three European universities co-developed a virtual mobility course with mutual ECTS recognition for their master students in educational sciences. It brings together instructors and students to synchronously collaborate on practical tasks of developing, designing, and evaluating a digital educational solution. Here, the two-year evolution of this collaborative project is reflected upon and analyzed through the lens of design-based research, giving insights into organizing, facilitating, teaching, and developing sustainable international courses.